Common issues on commercialization of genetically modified crops in Asia; a review / Mohd Khairi Abd Hamid - Abd Hamid, Mohd Khairi (Faculty of Plantation and Agrotechnology, 2018)
Genetically Modified Crops (GMC) commercialization has become one of the major issues in Asia country because of low food production and affected their economic life. Furthermore, the country like China, India, and Iran were the most country which has high population compared to other country like Malaysia. The objectives of this study are to review on the issue regarding GM Crop in Asia country and to extend knowledge on issues of commercialization in genetically modified crops for better precaution to the future. Without a doubt, GM Crop can help produce more foods to support people to survive in the future and prevent hunger in the community. The issues which concern Asian scientists, regulators and the lay public resemble those of other regions - biosafety, food safety, ethics, social justice, and regulation. Many of the remaining challenges to commercialization GM crops are related to the regulation and public acceptance. Most Asian countries now have regulatory systems for approving the commercialization of GM crops, and for approving food safety of GM crops. In Asia, because of the varied cultures, issues concerning the use of genes derived from animals arouse much emotion for religious and diet choice reasons. This is because many Asian producers and farmers are small-scale, there is also concern about technology dependency and to whom the benefits accrue.